Model Desain Pembelajaran Tematik Terpadu Kontekstual Untuk Meningkatkan Kebermaknaan Belajar Siswa SD - Mawardi Mawardi; Naniek Sulistya Wardani; Agustina Tyas Asri Hardini; Firosalia Kristin (Scholaria: Jurnal Pendidikan dan Kebudayaan, 2019)
This study aims to: 1) develop syntax of instructional contextual integrated thematic design models to improve the meaningful learning of elementary students; 2) describe an validity models; and 3) describe the level of effectiveness of the model. This R&D research consists of a preliminary study, model designing and developing to be validated by experts, the model testing. The preliminary field testing involved 4 teachers and 57 elementary students participants. The main field testing involved 8 teachers and 94 students. The research instrument are questionnaires and test. This research findings are: 1) the model steps includes: a) setting a theme; b) adding sub-themes; c) the analysis of SKL, KI, KD and making indicators; d) the making of nets of sub-themes; e) developing syllabus; f) developing RPP; g) compiling a fragment of the teacher's book; and h) developing fragments of student books; 2) the model validity level is in the very high category (86%), the syllabus and lesson plans and the material are in the high category (69.8%; 69%); and 3) the meaningfulness of student learning has increased, namely in the preliminary field test increased from 49.49 in pretest to 69.44 in post-test, and in the broad field test, the value increased greater than 47.98 to 70.43. The statistical test using the t-test ensures that the increase is significant, because the probability value (0.00) is smaller than the value of α = 0.05.